Insights for Deriving Induced Pluripotent Stem Cells in Marsh Deer (Blastocerus dichotomus) - Rola, Luciana Diniz [UNESP]; Bressan, Fabiana Fernandes; Sandoval, Eluzai Dinai Pinto [UNESP]; Therrien, Jacinthe; Smith, Lawrence Charles; Duarte, José Maurício Barbanti [UNESP] (MDPI, 2025)
The capability to generate induced pluripotent stem cells (iPSCs) from adult somatic cells, enabling them to differentiate into any cell type, has been demonstrated in several studies. In humans and mice, iPSCs have been shown to differentiate into primordial germ cells (PGCs), spermatozoa, and oocytes. However, research on iPSCs in deer is novel. Despite the necessity for establishing germplasm banks from endangered cervid species, the collection and cryopreservation of gametes and embryos have proven complex for this group. Therefore, the focus of this study was to establish protocols for deriving stable iPSC lines from Blastocerus dichotomus (Marsh deer) using primary cells derived from antler, adipose tissue, or skin, with the ultimate goal of producing viable gametes in the future. To achieve this, two main reprogramming approaches were tested: (1) transfection using PiggyBac transposons (plasmid PB-TET-MKOS) delivered via electroporation and (2) lentiviral transduction using the STEMCCA system with either human (hOSKM) or murine (mOSKM) reprogramming factors. Both systems utilized murine embryonic fibroblasts (MEFs) as feeder cells. The PiggyBac system was further supplemented with a culture medium containing small molecules to aid reprogramming, including a GSK inhibitor, MEK inhibitor, ALK/TGF inhibitor, and thiazovivin. Initial colony formation was observed; however, these colonies failed to expand post-selection. Despite these challenges, important insights were gained that will inform and guide future studies toward the successful generation of iPSCs in deer.